A Review of the Researchs of the Xishan Qinkuang - Zhang, Ruoye (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
Xishan Qinkuang, written by Xu Shangying, a famous zither player in the late Ming and early Qing dynasties, is a masterpiece of the aesthetic thought of guqin music in China, and it has a very high aesthetic value. The playing skills and aesthetic ideas of the qin contained in the book are very beneficial to the future generations in learning the skills of the guqin and studying the aesthetics of the qin, and also provide reference for the research of instrumental music and music aesthetics nowadays. This paper tries to sort out and summarize the research results of Xi Shan Qinkuang into four aspects, namely, aesthetic scope research, performance aesthetics research, aesthetics thought research, and research on the spirit of traditional Chinese art, with a view to generating new thoughts.